Impact behaviour of woven coir-epoxy composite: Effects of woven density and woven fabric treatment. (February 2016) - Azrin Hani, AR; Hashim, MS; Lim, TY; Mariatti, M; Ahmad, R
Several approaches have been implemented to enhance the impact performance of natural fibre-reinforced composite structures. The control of reinforcement structure and fibre modification through treatment are among the approaches. The objective of this study was to evaluate the impact behaviour of woven coir-epoxy composite as a function of fabric density and fabric modification using alkalisation treatment. Samples were subjected to low-velocity impact penetration tests and image analysis technique was used to measure the area and perimeter of the damaged samples under impact. A multi-level full factorial design was implemented in this study as a systematic and efficient way to distinguish the interactions of more than one factor. Two levels of woven density (Type 1 and Type 2) were investigated and four levels of treatment percentage (0%, 6%, 9% and 12%) were examined. Moreover, analysis of variance (ANOVA) was employed to determine the significant factors that predominantly influence the impact behaviour of woven composites. It was found that the differences in woven density and woven treatment significantly affect the maximum impact load and deflection of woven coir-epoxy composites. Impact energy absorption, however, was only affected by woven treatment. Factor interactions were also apparent for maximum impact load, initiation energy and deflection. The results showed that woven reinforcement with denser structure was less stiff in nature. The deformability of the composites was also found to reduce with the increase of treatment percentage. Furthermore, poor damage resistance was observed in denser woven structure.